Corrigendum to “Insight into zircon REE oxy-barometers: A lattice strain model perspective” [Earth and Planetary Science Letters 506 (2019) 87–96] - Zou, X.; Qin, K.; Han, X.; Li, G.; Evans, Noreen; Li, Z.; Yang, W. (Elsevier BV, 2019)
The authors regret that Formula 2 was incorrect and should appear as follows: [Formula presented] The authors would like to apologise for any inconvenience caused.